Pengalaman Pasien Hemodialisis yang Sudah Sembuh dari COVID-19 - Hariesty Talenta Narwastu Telaumbanua; Siti Zahara Nasution; Mula Tarigan (Jurnal Keperawatan Silampari, 2022)
This study aims to explore the experiences of Hemodialysis patients who have recovered from COVID-19 in Medan City. The research method used is a qualitative design with a phenomenological approach. The results of the study revealed six themes, namely 1). Coping Process, 2). Physical State, 3). Health Behavior, 4). Family Role and Support, 5). The Role of Nurses and Medical Actions, 6). Environmental Response to the Condition of Patients Experiencing COVID-19. In conclusion, the experience of Hemodialysis patients who have recovered from COVID-19 shows that while they are being treated in the isolation room, they experience various coping and handling processes that must be by health protocols and continue to undergo hemodialysis. Keywords: COVID-19, Hemodialysis, Patient Experience